The origin and early evolution of cytokinin signaling - Powell, Anahid E.; Heyl, Alexander (Frontiers in Plant Science, 2023)
Angiosperms, especially Arabidopsis and rice, have long been at the center of plant research. However, technological advances in sequencing have led to a dramatic increase in genome and transcriptome data availability across land plants and, more recently, among green algae. These data allowed for an in-depth study of the evolution of different protein families – including those involved in the metabolism and signaling of phytohormones. While most early studies on phytohormone evolution were phylogenetic, those studies have started to be complemented by genetic and biochemical studies in recent years. Examples of such functional analyses focused on ethylene, jasmonic acid, abscisic acid, and auxin. These data have been summarized recently. In this review, we will focus on the progress in our understanding of cytokinin biology. We will use these data to synthesize key points about the evolution of cytokinin metabolism and signaling, which might apply to the evolution of other phytohormones as well.